A user guide for the Excel interface to compute optimal tariff aggregators - Laborde Debucquet, David (International Food Policy Research Institute, 2015)
The AGRODEP Consistent Policy Aggregator Toolbox was created to assist users perform aggregation and tariff reduction senarios. Technical Note 13 provides documentation for the toolbox in the form of a user's guide, which includes information on the installation procedure, the utilization and data, and program files. This technical note is available for download here as well as part of the toolbox collection of files.